Limits of deception in Islamic laws of war: the case of civilian disguises in suicide attacks - Fajri Matahati Muhammadin (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam, 2020)
The suicide attack is an infamous method of warfare mostly associated with Islamic militant groups. While there are numerous aspects from which to discuss this method of warfare from a fiqh al-siyar (Islamic international law) perspective, this article specifically highlights suicide attacks when they disguise as civilians which they often do. Few contemporary jurists discuss this particular aspect of suicide attacks, and even those have mostly missed one issue: it might be an impermissible treasonous deception. This article explores whether suicide attacks disguising as civilians constitutes as an act of treason in fiqh al-siyar. It is found that such method of attack is not in itself treasonous therefore not in itself impermissible. However, suicide attacks disguising as civilians may become treasonous depending on the circumstances. Further, even when it is not treasonous it can be impermissible due to other reasons such as modern International Humanitarian Law (IHL), or maṣlaḥat.